2020
DOI: 10.1021/acs.analchem.0c00799
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Electrochemiluminescence of the Dichlorobis(1,10-phenanthroline)ruthenium(II) (Ru(phen)2Cl2)/Tri-n-propylamine (TPrA) System in H2O–MeCN Mixtures for Identification of Nucleic Acids

Abstract: Aggregation-induced electrochemiluminescence (AIECL) of the dichlorobis­(1,10-phenanthroline)­ruthenium­(II) (Ru­(phen)2Cl2)/tri-n-propylamine (TPrA) system was systematically investigated in H2O–MeCN media. Up to a 120-fold increase in the ECL intensity was observed when the H2O fraction (v%) was changed from 30% to 70%, whereas only an approximately 5.7-fold increase in the corresponding aggregation-induced fluorescence emission was demonstrated. The gradual formation of clusters of Ru­(phen)2Cl2 nanoaggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Very recently, aggregation-induced emission (AIE), a concept launched by Ben Zhong Tang and coworkers, 9,10 has been introduced into the ECL field as new-generation ECL emitter. [11][12][13][14][15][16][17][18][19] Impressively, as for those AIE luminogens, the ubiquitous aggregation caused quenching (ACQ) issue originating from notorious π-π interactions and/or molecular-motion-induced energy dissipation has been well solved via AIE effect. 10 For them, water-insolubility of organic molecules is not a drawback, but even becomes a premise and framework for constructing self-aggregated powder, film or crystalline solidstate emitters featuring much-enhanced PL quantum efficiency (ΦPL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, aggregation-induced emission (AIE), a concept launched by Ben Zhong Tang and coworkers, 9,10 has been introduced into the ECL field as new-generation ECL emitter. [11][12][13][14][15][16][17][18][19] Impressively, as for those AIE luminogens, the ubiquitous aggregation caused quenching (ACQ) issue originating from notorious π-π interactions and/or molecular-motion-induced energy dissipation has been well solved via AIE effect. 10 For them, water-insolubility of organic molecules is not a drawback, but even becomes a premise and framework for constructing self-aggregated powder, film or crystalline solidstate emitters featuring much-enhanced PL quantum efficiency (ΦPL).…”
Section: Introductionmentioning
confidence: 99%
“…Coincidentally, such property is extremely satisfactory for the development of a qualified aqueous ECL emitter, which is the essential demand of the whole ECL technique towards various kinds of applications. 2,20 Starting from the pioneer report on Platinum (II) complex in 2017 by Cola's group, 11 a variety of aggregation-induced electrochemiluminescence (AIECL) emitters have emerged, such as metallic complexes, 18,21,22 metal clusters, 23 AIE organic molecules 12,[14][15][16]24 , carbon dots 17 or polymer dots. 13,25 Meanwhile, ECL bioscience sensing studies using these emitters have also been developed, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Gu et al reported the use of dichlorobis(1,10-phenanthroline) ruthenium(II) ([Ru 2 (phen) 2 Cl 2 )] as AIECL luminophore and its application in the sensing and differentiation of nucleic acids [67]. The PL and AIECL emissions of [Ru 2 (phen) 2 Cl 2 ] aggregates, using TPrA as co-reactant, were found to be at a maximum in a 70% water:30% CH 3 CN mixture; at higher water content the increase in the size of the aggregates becomes counterproductive, and a decrease in the intensity of the AIECL is observed (Fig.…”
Section: Small Molecule-based Aieclmentioning
confidence: 99%
“…The encapsulation was achieved by the pH-triggered assembly-disassembly of apoFt. The Ir(ppy) 3 @apoFt bioconjugate was used to construct an immunosensor for the biomarker for squamous cell carcinomas CYFRA21, with a good linearity range (1 pg mL −1 -50 ng mL −1 ) and an interesting Adapted with permission from Gu et al [67]. Copyright 2020 American Chemical Society LOD (0.43 pg mL −1 ).…”
Section: Small Molecule-based Aieclmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) is one powerful sensing tool with high sensitivity (<10 –11 M) and outstanding stability for clinical diagnosis, , pharmaceutical analysis, food safety, and environmental monitoring . The key step was to excite the luminescent molecule [such as Ru­(bpy) 3 , bpy = 2,2′-bipyridine] by external power to form excited states via electron transfer, which could produce emission with coreactants as signal amplification.…”
Section: Introductionmentioning
confidence: 99%